Participatory Design of an Activities-Based Collective Mentoring Program in After-School Care Settings: Connect, Promote, and Protect Program - Milton, Alyssa C; Stewart, Elizabeth; Ospina-Pinillos, Laura; Davenport, Tracey; Hickie, Ian B (JMIR Publications, 2021)
BackgroundOut of school hours care (OSHC) services provide a unique opportunity to deliver early intervention programs to enhance primary school-aged children's social, emotional, physical, and cognitive well-being; however, such programs are currently lacking. ObjectiveThis study aims to address the lack of well-being programs for children accessing OSHC services in the research literature by using participatory design (PD) to collaboratively develop and test an OSHC well-being program-the connect, promote, and protect program (CP3). MethodsThe study employed methods of PD, user (acceptance) testing, and iterative knowledge translation to develop a novel well-being program framework-CP3-with key stakeholders (eg, children, OSHC staff, volunteers, families, clinicians, educators, and researchers). Thematic techniques were used to interpret and translate the qualitative information obtained during the research and design cycles. ResultsThe co-design process generated the CP3 model, which comprises a group-based mentoring approach to facilitate enhanced activities in OSHC settings. Activities are underpinned by 4 key principles of program delivery: build well-being and resilience, broaden horizons, inspire and engage, and connect communities. ConclusionsTo our knowledge, the CP3 program is the first co-designed well-being program developed specifically for OSHC services. This co-design process is key to ensuring local community needs-particularly those of young people accessing OSHC-are met and that these individuals are meaningfully and actively involved in all stages of the research and design process, from conception to implementation, evaluation, and continuous improvement.